THE ROLE OF USING COLLOCATIONS IN IMPROVING ENGLISH FLUENCY (Academia Science Repository, 2023)
This article provides information about English collocations, types, grammatical categories, examples and distinctions between strong, weak and fixed collocations. Furthermore, benefits of using collocations in different contexts to be more fluent speaker is explicitly clarified.